Faktor Yang Berhubungan Dengan Status Gizi Karyawan Minimarket - Nurhidayah Tiasya Sanas; Zulfitrawati Zulfitrawati; A Dhini Alfiani (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Background: Overnutrition is common in Indonesia, with 13.5% of adults being overweight and 28.7% being obese. Lack of physical activity, excessive food consumption, and high consumption of risky foods such as sugar, salt, and fat are risk factors for nutritional status Objective: To determine factors related to nutritional status in mini market employees Method: Researchers used a cross-sectional design in this study involving 99 respondents. The research began from September to October 2021. Data analysis used Fisher's test and logistic regression Results: Based on Fisher's test analysis, there was a significant relationship between salt intake (p=0.041), physical activity (p=0.002), and nutritional status. Meanwhile, no significant relationship was found between sugar and fat intake and nutritional status. The results of the logistic regression test show that the factor that has the most influence on nutritional status is excessive salt intake Conclusion: There is a relationship between salt intake, physical activity and nutritional status. Meanwhile, there was no relationship between sugar and fat intake and nutritional status. The factor most related to the nutritional status of employees in Makassar city mini markets is salt intake.